CALCIUM SUPPLEMENTATION IN THE PREVENTION OF HYPERTENSIVE DISORDERS OF PREGNANCY: INTEGRATIVE REVIEW - Nascimento , Bianca Thaís Silva do (2024)
This article aims to highlight calcium supplementation in the prevention of gestational hypertensive disorders. This is an integrative review, using the databases indexed in the Virtual Health Library (VHL): MEDLINE, SciELO, BDENF-Enfermagem and LILACS, using the descriptors: “Calcium supplementation”, “prevention”, “disorders hypertensive disorders during pregnancy” and “gestational hypertension”, in order to answer the question “What is the relevance of calcium supplementation in the prevention of gestational hypertensive disorders?”. As a result, calcium supplementation during pregnancy has shown promise for implementation in prenatal care protocols in view of the vulnerable population with low calcium nutritional intake, thus seeking to promote the prevention of hypertensive disorders in the perinatal period. . Concluding that through literature that supplementation in a guided manner and accompanied by trained health professionals, age reduces maternal gestational hypertension and, consequently, the risk of pre-eclampsia, in women with low previous calcium deficiency. However, although calcium supplementation appears to reduce blood pressure directly, it does not prevent endothelial damage associated with preeclampsia.